(untitled) (Revista Contexto & Educação, 2026)
This study is an excerpt from a master’s thesis in which we sought to understand how neoliberalism, understood as a rationality and as a policy of governing bodies, relates to Brazilian educational policies, specifically the New High School Reform (13.415/2017) and the National Common Curriculum Base based on discourses about mental health. With this, the aim is to analyze how the English language textbook of the new high school addresses psychological suffering, considering the intersection between mental health and neoliberal educational policies. Theoretically, it is based mainly on the studies of Michel Foucault and authors such as Deleuze (1992); Safatle, Silva Júnior and Dunker (2020); Dardot and Laval (2016); Navarro (2022) and Han (2015; 2018). Methodologically, this study has a descriptive-interpretative nature with a qualitative approach. The results allow us to understand that the textbook, being anchored in contemporary educational policies, is permeated by knowledge-power relations that disseminate discourses aimed at leading and guiding bodies towards productivity, resilience, discipline and efficiency, especially in the management of emotions and the regulation of mental health. The English language plays an important role in this context, as it is the language used to access the global market, and is also made compulsory by the BNCC.